El sistema de comunicación del Gobierno Autónomo Descentralizado Municipal de Alausí y su incidencia en la opinión pública de la población de este cantón comprendida entre los 20 a 50 años de edad durante el período diciembre de 2012 a mayo de 2013”. - Caguas Chafla, Mería Elizabeth (2016)
This research is to determine the incidence of Communicative System Decentralized Autonomous Government Municipal Alausi in public opinion of the local population aged 20 to 50 years old during the period December 2012 to May 2013. This study has divided into three segments purpose is the review of the literature regarding the epistemological foundations that support this study, a future field research and the proposal of a Communication Plan represents a real need for this town. This work consists of 5 chapters which are divided into topics and subtopics as follows: Chapter I contains the reference framework which shows the basics of research in this part of the study problem, objectives and rationale for a better understanding of the implications of the research is presented. Chapter II refers to the theoretical framework consisting of concepts and constructs concerning the subject matter. Chapter III covers the methodological framework that fits the type of research, techniques and tools for data collection, analysis and interpretation of results, among others. This chapter also designs the actions to be carried out within the research. Chapter IV, the conclusions and recommendations of the study based on the research results are presented. Chapter V addresses the proposed study involves the development of a Communication Plan for GADMC-Alausi, from institutional diagnosis and the interests and needs of the population, as a contribution to this public entity. And finally, the bibliography and annexes to conclude this paper is attached.